Effects of Bokashi and NPK on the Growth and Yield of Purple Eggplant Plants - Sulaminingsih; Ramayana, A. Syamad; Saka, Nurfaida (Postgraduate, University of Mataram, 2024)
This study evaluated the effect of bokashi from slaughterhouse waste and NPK compound fertilizer on the growth and yield of purple eggplant (Solanum melongena L.). The experiment was conducted in Sambaliung, Berau, for 4 months with a factorial Completely Randomized Design (CRD). Bokashi was given in five doses: B0 (control), B1 (5 MgHa-1), B2 (10 MgHa-1), B3 (15 MgHa-1), and B4 (20 MgHa-1). NPK fertilizer was applied in four doses: P0 (control), P1 (5 gr/polybag), P2 (10 gr/polybag), P3 (15 gr/polybag), and P4 (20 gr/polybag). The parameters observed included plant height, flowering age, and fruit weight per plant. Data were analyzed using ANOVA and Duncan's test at the 5% level. The results showed that the combination of bokashi and NPK had a significant effect on plant height, but not significant on flowering age and fruit weight. The use of bokashi and NPK effectively increases the growth of purple eggplant, so it can be an alternative for farmers to reduce dependence on NPK chemical fertilizers and switch to organic methods sustainably